The antitumor potential of Polygonatum spp.: a narrative review of traditional uses, bioactive metabolites, and multi-targeted mechanisms - Zhu, Mengqin; Chen, Guang; Li, Jinyu; Yi, Chang; Yuan, Yanfeng; Liu, Wenlong; Zhang, Xili (Frontiers in Pharmacology, 2025)
Polygonatum spp., encompassing various species within the genus, is a traditional Chinese botanical drug. It is known for its pharmacological effects, including qi tonification, yin nourishment, spleen invigoration, lung moistening, and kidney tonification. Polygonatum contains abundant bioactive metabolites, such as polysaccharides, steroidal saponins, flavonoids, volatile metabolites, and alkaloids. Recent research primarily revolves around its anti-inflammatory, anti-ageing, and glycaemic regulatory properties, while its antitumor potential remains comparatively underexplored. Malignant tumors represent a considerable global public health obstacle and are now a leading contributor to the global disease burden. The identification of effective antitumor agents and therapeutic strategies is urgent. Bioactive metabolites in Polygonatum have shown strong cytotoxic and pro-apoptotic impacts in vitro and in vivo. However, current research mostly focuses on isolated metabolites, lacking comprehensive narrative analysis. This review endeavors to narratively summarize recent advances on the antitumor activity and underlying mechanisms of Polygonatum, critically evaluate existing research gaps, and proposes future directions to facilitate the development of Polygonatum as a potential novel anticancer agent.